The impact of typhoons on economic activity in the Philippines: Evidence from nightlight intensity - Eric Strobl (Asian Development Bank (ADB), 2019)
We quantify the economic impact of typhoons in the Philippines. To this end we construct a panel data set of local economic activity derived from nightlight intensity satellite images and a cell level measure of typhoon damage constructed from storm track data, a wind field model, and a stylized damage function. Our econometric results reveal that there is a statistically and potentially economically significant, albeit short- lived, impact of typhoon destruction on local economic activity. Constructing risk profiles from a 60-year historical set of storms suggests that (near) future losses in economic activity for frequent (5-year return period) and rare (50-year return period) events are likely to range from between 1.0% and 2.5%.
Keywords: O17; O44; Q54; 330; economic impact; nightlights; Philippines; typhoons; wind field model